PENGARUH EKSTENSIFIKASI DAN INTENSIFIKASI TERHADAP PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI : (Studi Pada Kantor Pelayanan Pajak Pratama Kuningan) - maulana, robi; Dasuki, Tito (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The Majalengka Tax Service, Counseling and Consultation Office has changed its function to the Majalengka Micro Tax Service Office. This research is to find out how the Effect of Extensification and Intensification on Individual Income Tax Receipts at the Kuningan Pratama Tax Service Office.This research is a quantitative study using primary data with data collection techniques using questionnaires measured using a Likert scale. The population of this study were all employees of the Pratama Kuningan Tax Service Office. The sampling technique in this study used saturated sampling or census sampling with a total of 55 respondents who were studied. The data analysis technique used is multiple linear regression analysis techniques.The results of this study indicate that: Extensification has a significant effect on Individual Income Tax Receipts and Intensification has no significant effect on Individual Income Tax Receipts.